Non-Canonical Amino Acid-Based Engineering of (R)-Amine Transaminase - Pagar, Amol D.; Jeon, Hyunwoo; Khobragade, Taresh P.; Sarak, Sharad; Giri, Pritam; Lim, Seonga; Yoo, Tae Hyeon; Ko, Byoung Joon; Yun, Hyungdon (Frontiers in Chemistry, 2022)
Non-canonical amino acids (ncAAs) have been utilized as an invaluable tool for modulating the active site of the enzymes, probing the complex enzyme mechanisms, improving catalytic activity, and designing new to nature enzymes. Here, we report site-specific incorporation of p-benzoyl phenylalanine (pBpA) to engineer (R)-amine transaminase previously created from D-amino acid transaminase scaffold. Replacement of the single Phe88 residue at the active site with pBpA exhibits a significant 15-fold and 8-fold enhancement in activity for 1-phenylpropan-1-amine and benzaldehyde, respectively. Reshaping of the enzyme’s active site afforded another variant F86A/F88pBpA, with 30% higher thermostability at 55°C without affecting parent enzyme activity. Moreover, various racemic amines were successfully resolved by transaminase variants into (S)-amines with excellent conversions (~50%) and enantiomeric excess (>99%) using pyruvate as an amino acceptor. Additionally, kinetic resolution of the 1-phenylpropan-1-amine was performed using benzaldehyde as an amino acceptor, which is cheaper than pyruvate. Our results highlight the utility of ncAAs for designing enzymes with enhanced functionality beyond the limit of 20 canonical amino acids.